1996
DOI: 10.1111/j.1432-1033.1996.t01-1-00827.x
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cysteine‐Rich Secretory Protein (CRISP) Family

Abstract: We report the isolation and characterisation of cDNAs encoding three different, human members of the cysteine-rich secretory protein (CRISP) family. The novel CRISP-I exists in five cDNA subtypes differing by the presence or absence of a stretch coding for a C-terminal cysteine-rich domain so far found in all members of the family, and by the length of their 3'-untranslated region. CRISP-2 cDNA corresponds to the previously described TPXI form, with so far unreported 5'-untranslated sequence heterogeneities wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
151
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(160 citation statements)
references
References 44 publications
5
151
0
4
Order By: Relevance
“…As evidenced by Northern blotting, Crisp2 is most abundantly expressed in the testis (Kasahara et al, 1989;Kratzschmar et al, 1996;O'Bryan et al, 1998). Crisp2 is not regulated by androgens and its mRNA is first expressed in pachytene spermatocytes (Haendler et al, 1997;O'Bryan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As evidenced by Northern blotting, Crisp2 is most abundantly expressed in the testis (Kasahara et al, 1989;Kratzschmar et al, 1996;O'Bryan et al, 1998). Crisp2 is not regulated by androgens and its mRNA is first expressed in pachytene spermatocytes (Haendler et al, 1997;O'Bryan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this potential activity is currently unknown, but the addition of peptides corresponding to the CAP domain signature motifs and cell transfection experiments using truncated forms of CRISP2 suggest that there is a CAP protein involved in sperm-oocyte binding via the CAP domain (Maeda et al, 1999;Ellerman et al, 2006). Northern blotting data from several species shows that Crisp1 is most abundantly expressed in the epididymis (Charest et al, 1989;Haendler et al, 1993;Kratzschmar et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRISP3 is expressed at low levels in normal human prostate and strongly upregulated in a fraction of prostate cancers. [3][4][5][6] The clinical relevance of CRISP3 overexpression is controversially discussed. Some studies found CRISP3 overexpression to be associated with increased risk of tumor recurrence, 7 unfavorable tumor phenotype, 8,9 castration-resistant prostate cancer, and metastasis, 9,10 whereas others could not find any clinically relevant associations.…”
mentioning
confidence: 99%